Synthesis and Anti‐Inflammatory Activity of 2‐Amino‐4, 5, 6, 7‐tetrahydrobenzo[b]thiophene‐Derived NRF2 Activators. Issue 10 (25th October 2022) - Mak, Kit‐Kay; Shiming, Zhang; Epemolu, Ola; Dinkova‐Kostova, Albena T.; Wells, Geoffrey; Gazaryan, Irina G.; Sakirolla, Raghavendra; Mohd, Zulkefeli; Pichika, Mallikarjuna Rao
Abstract: This is the first study investigating the nuclear factor (erythroid‐derived 2)‐like 2 (NRF2) activity of compounds containing a new scaffold, tetrahydrobenzo[ b ]thiophene. Eighteen compounds were synthesised and confirmed their NRF2 activation through NQO1 enzymatic activity and mRNA expression of NQO1 and HO‐1 in Hepa‐1c1c7 cells. The compounds disrupted the interaction between Kelch‐like ECH‐associated protein 1 (KEAP1) and NRF2 via interfering with the KEAP1's Kelch domain. The compounds exhibited anti‐inflammatory activity in Escherichia coli Lipopolysaccharide (LPS Ec )‐stimulated RAW 264.7 cells. The anti‐inflammatory activity of the compounds was associated with their ability to activate NRF2. The compounds reversed the elevated levels of pro‐inflammatory cytokines (IL‐1β, IL‐6, TNF‐α, and IFN‐γ) and inflammatory mediators (PGE2, COX‐2, and NF‐κB). The compounds were metabolically stable in human, rat, and mouse liver microsomes and showed optimum half‐life (T1/2 ) and intrinsic clearance (Clint ). The binding mode of the compounds and physicochemical properties were predicted via in silico studies. Abstract : 2‐Amino‐4, 5, 6, 7‐tetrahydrobenzo[ b ]thiophenes activate NRF2 via a non‐electrophilic mechanism. They inhibit LPS Ec ‐stimulated inflammation in macrophages and are moderately stable in liver microsomes. The most active compounds′ binding interactions and conformations with KEAP1 were predicted using docking and molecular dynamics studies.